Construction of social vulnerability index in Indonesia using partial least squares structural equation modeling - Kurniawan, Robert; Hadumaon Siagian, Tiodora; Yuniarto, Budi; Ilmi Nasution, Bahrul; Eko Caraka, Rezzy (International Journal of Engineering and Technology, 2019)
Social Vulnerability Index (SoVI) is a valuable tool for comparing differences across communities in their overall capacity to prepare for, respond to and recover from natural hazards. Due to its benefits for policymakers and practitioners, SoVI has been widely applied in many countries. Many researchers utilized Exploratory Factor Analysis (EFA) method in SoVI construction. However, the theory says that data from items for EFA have to be normally distributed. In the heart of statistics, not all data follows the Normal distribution. As normality assumption is not a requirement for using Partial Least Squares Structural Equation Modeling (PLS-SEM) method, therefore, this study tries to show the use of PLS-SEM method for SoVI construction. In this study, we utilized reflective formative second order hierarchy model and revealed that many regencies/municipalities with high levels of social vulnerability which located in the Eastern region of Indonesia. These findings highlight the crucial need for strengthening development in the Eastern region of Indonesia.Â Â